Analysis of Workplaces Supply in a Production Company - Vieroslav, Molnár; Průša, Petr; Jan, Strohmandl; Michal, Legát (EDP Sciences, 2017)
The paper deals with the analysis of the supply of workplaces and the description of the related activities. Workplaces are supplied using specific supply means. The individual supplies used in the supply system, a description of the main activities and the principle of work are characterized. There are five alternative proposals for improving the supply of production workplaces. A proportional index method was used to select the optimal variant of the supply solution for the production workplaces. The optimal solution proposal is to add the transport lanes in the production hall.
Analýza dodávek k pracovním místům ve výrobní firmě
Keywords: Analysis; Workplaces; Supply; Production; Company; Analýza; dodávky; pracovní místo; výrobní firma